Serum Biomarkers in Transthyretin Amyloidosis: An Overview of Neurofilaments, Cardiac, Renal, and Gastrointestinal Involvement - Valeria Guglielmino; Francesca Vitali; Angela Romano; Guido Primiano; Maria Ausilia Sciarrone; Marco Luigetti (Neurology and Therapy)
Abstract Hereditary transthyretin amyloidosis (ATTRv, v for variant) is a genetic disorder characterized by the deposition of misfolded transthyretin (TTR) protein in tissues, resulting in progressive dysfunction of multiple organs, including the nervous system, heart, kidneys, and gastrointestinal (GI) tract. Noninvasive serum biomarkers have become key tools for diagnosing and monitoring ATTRv. This review examines the role of available biomarkers for neurological, cardiac, renal, gastrointestinal, and multisystemic involvement in ATTRv. A thorough understanding of these biomarkers is essential for effective disease management and therapeutic monitoring.